2020
DOI: 10.35808/ersj/1678
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Reform and IPSAS Adoption in Greece

Abstract: Purpose: The study aims to investigate the level of acceptance and preparation of the Local Administration Organizations regarding the adoption of International Public Sector Accounting Standards (IPSAS) in Greece. Design/Methodology/Approach: In order to accomplish this purpose a survey was realized by addressing a questionnaire to officers and employees of the finance department of 325 municipalities in Greece and to the elected representatives who are responsible for their financial management and reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Extant literature points towards functionalist (e.g. achieving higher performance: Brunsson et al, 2012, or receiving better conditions when borrowing on the credit market: Chytis et al, 2020) and institutionalist perspectives (coercive, normative and mimetic isomorphic pressures to gain and maintain organizational legitimacy; Jorge et al, 2020;Oulasvirta, 2014;Tagesson, 2015). Coercive pressures are particularly relevant for emerging economies (stemming from donor organizations), as, e.g.…”
Section: Standardization Deviations and Practice Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant literature points towards functionalist (e.g. achieving higher performance: Brunsson et al, 2012, or receiving better conditions when borrowing on the credit market: Chytis et al, 2020) and institutionalist perspectives (coercive, normative and mimetic isomorphic pressures to gain and maintain organizational legitimacy; Jorge et al, 2020;Oulasvirta, 2014;Tagesson, 2015). Coercive pressures are particularly relevant for emerging economies (stemming from donor organizations), as, e.g.…”
Section: Standardization Deviations and Practice Variationmentioning
confidence: 99%
“…The objective of IPSAS is "to ensure comparability both with the entity's financial statements of previous periods and with the financial statements of other entities" (IPSASB, 2020, p. 163). Another expected positive effect of comparability is favourable conditions for borrowers on credit markets (ACCA, 2017;Chytis et al, 2020), so governments are expected to have an interest in aligning their national counterparts with these established international standards.…”
Section: Introductionmentioning
confidence: 99%
“…The literature refers to potential benefits of IPSAS adoption, such as increasing accountability and transparency, the comparability among governments or the legitimacy of the standards and, therefore, of governments that implement them (Castañeda-Rodriguez, 2022;Christiaens et al, 2015;EC, 2013;IPSASB, 2020;Kartiko et al, 2018;Manes-Rossi et al, 2016;Oulasvirta, 2021). Another impetus for the IPSAS use can be the favorable effects of comparability for borrowing on credit markets (ACCA, 2017;Chytis et al, 2020). Under this favorable environment for IPSAS adoption, and following some mimetic and coercive effects (DiMaggio and Powell, 1991), many countries have reformed their accounting systems in line with international standards (Brusca et al, 2015;Brusca and Martinez, 2016;Christiaens et al, 2015;Gom ez-Villegas et al, 2020;Kartiko et al, 2018;Polzer et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2016; Oulasvirta, 2021). Another impetus for the IPSAS use can be the favorable effects of comparability for borrowing on credit markets (ACCA, 2017; Chytis et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to that studies have been carried out in different areas within and outside Nigeria on adoption of IPSAS and financial reporting quality. The studies of (Brusca, et al, 2015;Tanjeh, 2016;Pena & Franco, 2017;Zhuquan and Javed, 2018;Ababneh et al, 2019;Zandi & Abdullah, 2019;Chytis et al, 2020;Bashir & Amir, 2020) were conducted in foreign countries like Indian, Asia, Kenya, Nepal, Bangladesh, Pakistan and Sri Lanka and found that adoption of IPSAS has moderate effect on the quality of financial reports in public sector. While (Obara& Efeeloo, 2017;Okere et al, 2017;Abimbola et al, 2017;Ademola et al, 2017;Akinleye et al, 2018;Olola , 2019;Obineme et al, 2021;ThankGod et al, 2021) conducted their studies in various states and local government in Nigeria like; Ondo, Ekiti, Oyo, Anambra and some other States in Nigeria and found that adoption of IPSAS increases the level of financial reporting quality.…”
Section: Introductionmentioning
confidence: 99%